2016
DOI: 10.1016/j.molcel.2015.11.020
|View full text |Cite
|
Sign up to set email alerts
|

Lin28A Binds Active Promoters and Recruits Tet1 to Regulate Gene Expression

Abstract: Lin28, a well-known RNA-binding protein, regulates diverse cellular properties. All physiological functions of Lin28A characterized so far have been attributed to its repression of let-7 miRNA biogenesis or modulation of mRNA translational efficiency. Here we show that Lin28A directly binds to a consensus DNA sequence in vitro and in mouse embryonic stem cells in vivo. ChIP-seq and RNA-seq reveal enrichment of Lin28A binding around transcription start sites, and a positive correlation between its genomic occup… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(68 citation statements)
references
References 38 publications
2
66
0
Order By: Relevance
“…Although LIN28B is documented to inhibit miRNA maturation, the present study showed that LIN28B knockdown reduced the expression of several C19MC miRNAs. These unexpected results may be explained by a recent study demonstrating that LIN28 binds directly to a consensus DNA sequence at promoter regions and recruits the CpG demethylase TET1 to activate transcription (58). Moreover, analysis of published PAR-CLIP results indicate that LIN28B can bind to CpG rich-Alu repeats dispersed throughout C19MC (29) that can function as independent promoters for RNA polymerase III and transcriptionally activate C19MC (59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…Although LIN28B is documented to inhibit miRNA maturation, the present study showed that LIN28B knockdown reduced the expression of several C19MC miRNAs. These unexpected results may be explained by a recent study demonstrating that LIN28 binds directly to a consensus DNA sequence at promoter regions and recruits the CpG demethylase TET1 to activate transcription (58). Moreover, analysis of published PAR-CLIP results indicate that LIN28B can bind to CpG rich-Alu repeats dispersed throughout C19MC (29) that can function as independent promoters for RNA polymerase III and transcriptionally activate C19MC (59)(60)(61).…”
Section: Discussionmentioning
confidence: 99%
“…As an important epigenetic modification enzyme, Tet1 interact with other proteins by forming protein complex58, transcription factor Lin28 regulate gene expression through recruitment of TET159. An active DNA demethylation process occurs with an involvement of TET enzymes, and the expression level of TET1–3 is critical for human spermiogenesis and male fertility31.…”
Section: Discussionmentioning
confidence: 99%
“…In mouse ESCs, LIN28A could recruit and form a complex with TET1 to promote 5mC‐to‐5hmC conversion and demethylation at 5′ upstream region of genes (Zeng et al, ). When we treated GmGSCs‐I‐SB cell line with 2 μM 5‐azacytidine (an inhibitor of DNA methylation), the NANOG expression was upregulated significantly (Figure a), which indicated that DNA demethylation was probably involved in the activation of NANOG transcription.…”
Section: Resultsmentioning
confidence: 99%